Industry-Level Disparities in Antitrust Enforcement - Md. Mominul Islam; Imrul Hossain Chowdhury; Sabrina Islam (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- The purpose of this study is to analyze whether an increase in the concentration of industry causes an increase in the level of the Department of Justice Antitrust Division (DoJ)’s antitrust enforcement within that industry. Design/Methodology- The study employed secondary data and quantitative research method was also utilized to achieve the objectives of the study. Multiple regression analysis techniques were used to analyze the data. Findings- The results support the hypothesis that an increase in the concentration of industry causes an increase in the level of Department of Justice Antitrust Division (DoJ)’s antitrust enforcement within that industry. It appears that industry-level revenue from exports is highly correlated with the size of that industry and its lobbying activity. Practical Implications- These results have practical relevance which helps to predict the intensity of antitrust activity in future years. Its practical implication is that there are disparities in antitrust enforcement that are influenced by factors other than concentration. By creating a benchmark that takes into account components such as this, the Department of Justice Antitrust Division (DoJ) can identify those companies who are likely to be engaging in anticompetitive behavior.